Exploring organizational aspects that promote health-related preventive behavior: using the example of work-related SARS-CoV-2 infection control measures in Germany, August 2020 to November 2021 - Soeder, Jana; Wagner, Anke; Neunhöffer, Anna T.; Martus, Peter; Papenfuss, Falko; Wittich, Andrea; Schwille-Kiuntke, Juliane; Rind, Esther; Rieger, Monika A. (Frontiers in Public Health, 2024)
Introduction: During the communicable coronavirus disease (COVID-19) pandemic, organizational infection control measures (oICM) were introduced in the workplace. The employees’ positive attitudes and active participation are relevant for full effectiveness regarding disease prevention. Therefore, we explore changes in employees’ attitudes toward oICM at work from Aug-Oct 2020 (T0) over January 2021 (T1) to Oct-Nov 2021 (T2). We further investigate the role an organization can play in supporting health-related preventive behavior. Methods: We considered repeated cross-sectional and longitudinal panel survey data from 5,554 employees of a global supplier of technology and services in Germany. 16 items constitute the attitude scores toward oICM (5-point Likert scale). Via mixed-effect model, aspects associated with employees’ attitudes toward oICM were explored. Via ‘extreme-group’-approach, we compared the 20% of participants with the largest changes into less favorable to the 20% with the largest changes into more favorable attitudes toward oICM over time. Results: The overall positive attitudes toward work-related oICM were more favorable at T1 (mean±SD: 4.2±0.6, median (IQR): 4.3 (0.8), n=2515) compared to T0 (4.1±0.6, 4.1 (0.8), n=2417) but less favorable at T2 (3.9±0.7, 4.0 (0.9), n=2062). Among others, feeling well-informed about possible work-related risks of infection with the severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2), perceived psychosocial demands through work environment aspects, and perceived management’s commitment to safety and health were associated with long-term positive attitudes toward oICM. Individuals developing more favorable attitudes toward oICM reported feeling well-informed about possible work-related SARS-CoV-2-infection risks and improved COVID-19-specific resilience over time. Individuals developing less favorable attitudes toward oICM reported decreased perceptions of COVID-19-associated risks. Conclusion: oICM in the workplace were perceived appropriate even after COVID-19 vaccines were widely available and although the perceived affective risks about SARS-CoV-2 decreased. Taken together, our findings highlight how organizations can support employees in adopting health-related preventive behavior. Among others, we found that feeling well-informed about possible work-related health risks was positively associated with long-term favorable attitudes toward work-related oICM. We expect that the results contribute to the development of interventions to prepare and adapt to future global public health concerns.